Analyzing the Moral Values Found In “Pathway to English” Textbook - Enjun Junaedi; Mustasyfa Thabib Kariadi; Novita Pri Andini (LPPM Universitas Pekalongan, 2026)
Moral values are an important aspect of students learning to make them a good individual. One of the ways to teach moral values is by reading narrative text. This study aimed to; (1) analyze the moral values contained in the narrative texts of the “Pathway to English” for grade 12 students, and (2) determining the most dominant moral value based on Michele Borba’s framework. This research employed qualitative content analysis steps suggested by Cohen, Manion, and Morrison (2007), and used a purposive sampling technique to select the two longest narrative texts: “The Withes by Roald Dahl” and “Busy Raindrops”. The selection of these text was based on the assumption that longer texts provide richer content, have longer narrative with more developed character, conflicts, and resolution, which are key elements in conveying moral lessons (Krippendorff, 2018; Neuendorf, 2017). The results of the analysis showed that of the seven Borba’s moral values in the text “The Withes by Roald Dahl”, was kindness, and in the text “Busy Raindrops”, the moral values found were fairness, respect, kindness, empathy, and self-control. Therefore, from these two texts, there were five types of moral values found: self-control, fairness, respect, kindness, and empathy. From these five types of moral values, kindness is the most dominant moral value with 50% occurrences, while the other moral values such as fairness, respect, self-control, and empathy have 12.5% occurrences for each of them. On the other side, the rest of moral values based on Borba’s framework, such as conscience, and tolerance were not found in the texts. These findings conclude that the moral values in the two narrative texts emphasize kindness. The texts promoting the importance of caring for others and treat them in a just way. However, the absence of certain moral values indicates the need for other texts or materials to supplement the balance of moral education.